The discoveries associated with the name of Claude Bernard and their results - MacLaren, Duncan W. (The University of Edinburgh, 1926)
[Hand-written]
The discoveries associated with the name of Claude Bernard and their results: submitted for the Wellcome Prize in the History of Medicine